Advanced process monitoring and feedback control to enhance cell culture process production and robustness. Issue 12 (4th September 2015) - Zhang, An; Tsang, Valerie Liu; Moore, Brandon; Shen, Vivian; Huang, Yao‐Ming; Kshirsagar, Rashmi; Ryll, Thomas
ABSTRACT: It is a common practice in biotherapeutic manufacturing to define a fixed‐volume feed strategy for nutrient feeds, based on historical cell demand. However, once the feed volumes are defined, they are inflexible to batch‐to‐batch variations in cell growth and physiology and can lead to inconsistent productivity and product quality. In an effort to control critical quality attributes and to apply process analytical technology (PAT), a fully automated cell culture feedback control system has been explored in three different applications. The first study illustrates that frequent monitoring and automatically controlling the complex feed based on a surrogate (glutamate) level improved protein production. More importantly, the resulting feed strategy was translated into a manufacturing‐friendly manual feed strategy without impact on product quality. The second study demonstrates the improved process robustness of an automated feed strategy based on online bio‐capacitance measurements for cell growth. In the third study, glucose and lactate concentrations were measured online and were used to automatically control the glucose feed, which in turn changed lactate metabolism. These studies suggest that the auto‐feedback control system has the potential to significantly increase productivity and improve robustness in manufacturing, with the goal of ensuring process performance and product quality consistency. Biotechnol. Bioeng. 2015;112: 2495–2504. © 2015 Wiley Periodicals, Inc. Abstract : The comparison between cIBC based auto feed and fixed feed at low seed density. The cIBC auto‐feedback control low seed process showed similar performance as the control regular seed process. However, the fixed feed low seed process crashed earlier due to over‐feeding.